PENERAPAN KNOWLEDGE MANAGEMENT SYSTEM BERBASIS INFORMASI DESA UNTUK MENINGKATKAN LAYANAN PUBLIK DESA DUKUH KARYA - Purwantoro Purwantoro; Yuyun Umaidah; Ultach Enri (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2018)
The rank of EGDI level (E-Government Development Index) in Indonesia has decreased and it reflects the development conditions of EGovernment in Indonesia are not maximally covering: the level of public services, there is a disparity in public services in the village, the support of information technology devices is still limited, the absence of village archive management, the absence of a system that can manage knowledge, there is no synergy between village apparatus. Dukuh Karya is a village that belongs to Karawang Regency, Rengasdengklok District. Dukuh Karya village has a population of around 6000 and mostly the residents has income from agricultural products. The need for knowledge managers in the village is to manage properly and implement a Knowledge Management System (KMS) based on village information systems can improve public services in the Dukuh Karya village. By applying the concept of KMS to be able to collect and manage all available knowledge. Building Knowledge, collect, store and use it so that the village government can be more transparent and accountable to improve public services. The implementation of KMS is a way for village apparatus to identify, create, represent, distribute, and enable the adaptation of insights and experiences consisting of knowledge, both owned by individuals and knowledge that is inherent in the process or standard of service procedures that have the main objective to maintain and effectively transfer knowledge that is important to improve the quality of service of village government apparatus to its citizens.